2022
DOI: 10.1177/20420188221139101
|View full text |Cite
|
Sign up to set email alerts
|

MAFLD: what 2 years of the redefinition of fatty liver disease has taught us

Abstract: Metabolic dysfunction–associated fatty liver disease (MAFLD) has appeared as the leading liver disease worldwide. Whereas the terminology nonalcoholic fatty liver disease (NAFLD) mainly reflected a negative selection and exclusion of alcohol-related liver disease (ALD), the new definition made its focus on the association of MAFLD with overweight/obesity, type 2 diabetes and metabolic risk factors especially also in normal weight/lean subjects. Several studies from the past 2 years have now used the new defini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…These findings were similar to our results that TFQI FT4 was positively associated with the prevalence of diabetes in euthyroid adults in the United States rather than in China. In addition, previous studies have reported significant associations of TFQI FT3 , but not TFQI FT4 , with MAFLD and NAFLD [ 19 , 40–42 ]. However, investigations into the associations between TFQI FT3 and diabetes were limited.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were similar to our results that TFQI FT4 was positively associated with the prevalence of diabetes in euthyroid adults in the United States rather than in China. In addition, previous studies have reported significant associations of TFQI FT3 , but not TFQI FT4 , with MAFLD and NAFLD [ 19 , 40–42 ]. However, investigations into the associations between TFQI FT3 and diabetes were limited.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several researchers have opted the newly coined term “MAFLD,” replacing the previous NAFLD term. The redefinition reflects substantial information gained from previous studies on the association between fatty liver and overweight/obesity, type 2 diabetes, and metabolic risk factors [ 31 33 ]. We also like to use the term MAFLD, instead of NAFLD or fatty liver, as this term more accurately emphasizes cardiovascular risks in patients with CHC [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many clinicians treat NAFLD as one of the components of metabolic syndrome (MS), with particular emphasis on the coexistence of this pathology with obesity and impaired glucose and/or lipid metabolism [ 3 , 4 ]. This approach led to the introduction of the concept of metabolic-associated fatty liver disease (MAFLD) [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%